Replenishing Water Source for Wildlife Using Hybrid Energy Sources - Nandhini Priya, T.; Nagaraj, B. V.; Kammar, Ramakrishna; Sanketha (Asian Journal of Electrical Sciences, 2019)
This Paper presents the hybrid model of solar and wind turbine system for the power generation.The hybrid system can be used in forest area and in the remote area also which is unable to connect to the grid and its use can be extended to city streets lights also. It can also be operated as a standalone PV and wind models. The hybrid model is designed using MATLAB Simulink.